Pengaruh Model Problem Based Learning (PBL) dan Minat Belajar terhadap Hasil Belajar Siswa Kelas IV SD Katolik 03 Frater Don Bosco Manado - Sarudi, Regina Kezya; Tiwa, Tellma Monna; Monigir, Non Norma (Jurnal Simki Pedagogia, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model and Learning Interest on the Learning Outcomes of Grade IV Students of SD Katolik 03 Frater Don Bosco Manado. This type of research is quantitative with a Pretest-Posttest Control Group design. The sample taken was 25 students of grade IV A as the control class and IV B as the experimental class. The data collection technique used tests and non-tests, then the data obtained was analyzed using the hypothesis I test and hypothesis II using the t test. The results of the study obtained an average value of the posttest learning outcomes of the experimental class which was higher, namely 74.28 and 90.44. While the control class values were 69.92 and 87.72. Based on the data analysis, the findings of this study indicate that the Problem Based Learning (PBL) model is effective for student interest in the learning outcomes of grade IV students on the procedural text material in learning Indonesian at SD Katolik 03 Frater Don Bosco Manado.